Editorial - Paddaja Roy; Kalyani Rava Devi (Transcript: An e-Journal of Literary and Cultural Studies)
The present issue (vol. 5, no. 1) of the transcript: An e-Journal of Literary and Cultural Studies is a collection of eight research articles out of which six articles focus on the thematic aspect of representation on Precarity in Literature, and two articles are open submissions. In the opening article, Nurten Birlik and Ataberk Çetinkaya analyse Zadie Smith's novel Swing Time by highlighting how underprivileged individuals living in London and Africa face precarity with translocality characterizing their porous experiences and how they cope with it through non-verbal, bodily and cultural practices that help them find meaning, stability and resilience. In the next article, Meetu Bhatia Kapur Kapur and Rumi Roy examine the nexus among precarity, hybridity, and resistance in The Glass Palace within the colonial and postcolonial landscape to explore how the characters navigate the fragile space between erasure and resistance in a world where belonging is perpetually deferred. In the next article Kankana Bhowmick examines Gun Island through the lens of human vulnerability to focus upon precarious societies and global displacement caused by climate/environmental crises and the effects of neoliberal capitalism. Dwitiya Sarkar and Jabbar Al Muzzamil Fareen’s paper explores the intersection of Tierratrauma, myth, and environmental restoration in Easterine Kire’s Son of the Thundercloud advocating the recognition of myth and storytelling as a compelling tool in connecting with Nature and addressing climate change and sustainability. Abhilasha Roy engages with texts such as Em and the Big Hoom (2012) and Choi’s Yolk (2021) to underscore how caring for a loved one becomes a direct exercise in facing one’s lived precarity and highlights how caregivers exemplify the precarity of gendered, racialised and working-class subjects in late capitalist societies. Syeda Shehnaz’s article intersects precarity and capitalism to analyse the necessity of utopian thought as a counter-narrative to the conditions of climate change and vulnerability rendered by precarity and capitalism. Dr. Kaptan Singh has conducted a lyrical content analysis of the most viewed Punjabi pop songs on YouTube between 2011 to 2020 to examine aggressive lyrical content of Punjabi pop songs. The analysis focuses on interpretation of the lyrical content of the songs in combination with narratological investigation to examine their structure and function to identify categorization and quantify the content. Karl Gustav Korsgaard-Klausen in his paper assesses the narratorial qualities of Moby-Dick and examines the first-person retrospective narration of the novel and its role in enlarging the whale to its aphorical enormity.